CONFIGURATION ET MISE EN PLACE D’UN RESEAU VPN DANS UNE ENTREPRISE. CAS DE LA BRALIMA /KISANGANI - MUTSUVA, Christian NZANZU (IJRDO -Journal of Computer Science Engineering, 2023)
This article looks at the implementation of a secure solution to enable secure and confidential communication between various remote sites and the Bralima Kisangani head office, using VPN technology developed under the Windows Server 2012 R2 environment. The choice of technology made in this study is based on several tunneling protocols offered by the Windows Server 2012 R2 environment, and offers ease of deployment and configuration. Two methodological approaches were used in this article, the first being analytical, focusing on modeling the existing system with a view to proposing a solution adapted to this company's needs. The last approach, descriptive, enabled us to describe in the most explicit way the VPN technologies implemented in the Windows Server 2012 R2 environment. This article outlines the elements that make up a VPN network and explains the various steps involved in configuring it.